Close encounters with humankind : a paleoanthropologist investigates our evolving species - Lee, Sang-Hee; Yoon, Shin-Young (W.W. Norton & Company, 2018)
Explores how the field of paleoanthropology enables insights into some of the world's leading evolutionary questions, exploring such topics as the life cycles of ancient people, the origins of social nature, and the common traits between modern humans and Neanderthals.